KUALITAS ANALISIS KUALITAS ASSURANCE STATEMENT ATAS LAPORAN KEBERLANJUTAN PERUSAHAAN DI BURSA EFEK BEBERAPA NEGARA DI DUNIA TAHUN 2020-2022 - Carmel Meiden; Gavriel Faith Nangoy; Suheriyatmono; Eddy Winarso; Sintong Mangadarmuda Harahap (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
While sustainability reporting has experienced notable advancements in recent years, a discernible gap persists between the progress in reporting practices and the corresponding assurance measures. This paper emphasizes the degree to which the contents of sustainability assurance statements align with the essential elements mandated by the ISAE 3000 and AA1000AS assurance standards. A content analysis was performed for the assurance statements of ten (10) public listed companies in the financial sector listed on 6 different exchanges over a three-year span from 2020 to 2022. This analysis employed a quantitative approach involving scoring to assess the alignment of the content with the requirements of the assurance standards. The research instrument used were based on the minimal content elements of ISAE 3000 and AA1000 AS and developed by previous studies. The results of this study describe variability in the quality of assurance statements based on assurance standards, assurance provider, country of origin, and content element. This research contributes to the existing literature in sustainability assurance through content analysis offering a nuanced global perspective through a streamlined research instrument derived from previous studies, enhancing the precision and conciseness of the analysis.